UPAYA MENURUNKAN STRES DAN MENINGKATKAN EFIKASI DIRI ORANGTUA DALAM MERAWAT ANAK RETARDASAI MELALUI PEER SUPPORT GROUP (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2023)
Caring for and raising a child mental retardation is an extraordinary and highly emotional experience and cause many difficulties for parent. Long-term care, perhaps even a lifetime, can be stressful and often affects family functioning as a whole. Stress on parent greatly affects parenting patterns and their ability to educate with mental retardation. Children who are raised with pressure will affect their development. Parent who are not confident in raising children are more emotional, nor assertive, do not care about children and are unable to treat children appropriately. Parenting Self Efficacy (PSE) is one way to measure the ability of parents to raise children. Self-efficacy can affect a person when facing stress or difficult situations and affect the behavior of parent in raising and loving their children. One form of support that can be done is by means of a Peer Support Group (PSG). Peer Support Group is a collection of similar groups that carry out activities with the aim of improving coping, providing social support, sharing experiences, reducting fear, and anxiety. The result of the activity showed that there was a decrease in stress on parent and an increase in PSE where the stress level before intervention was 44 with the high stress category and after the intervention decrease 68 with the low stress category. And PSE before the 64.1 intervention was in the low category, that parent was less able to care for their children, and after the 41.6, it was in the high category, that the able of parent to care for their children well increase. Recommended for Extraordinary School (SLB) teachers to facilitate Peer Support Group activities and be directly invoved in these activities.